Rancang Bangun Timbangan Buah Digital Berbasis Mikrokontroler Dengan Koneksi Printer Thermal - Muhammad Irmansyah; M Irmansyah; Milda Yuliza; Junaldi Junaldi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
This study aims to create a digital scale using a load cell sensor controlled by a microcontroller with a thermal printer connection. Load cell sensors, keypad, LCD, I2C Module, Thermal Printer and Arduino are used in hardware design. The Parallax Data Acquisition tool (PLX-DAQ) application is used to display and store data in excel form. The test results obtained that the load cell load 0 kg - 3 kg for every 1 kg increase in load weight, there will be a change in the output voltage of about 0.5 mV. The larger the load being measured, the greater the output voltage. The average measurement error rate is 2.07%, while the success rate for digital scales is 97.72%. Overall the digital scale works well.